Enhancing Elderly Participation and Well Being through User Centered and Social Features in Community Digital Education Programs - Xian Siying; I Gde Wawan Sudatha (Jurnal Media dan Teknologi Pendidikan, 2026)
The low participation of older adults in digital education programs remains a challenge in achieving educational equity and social inclusion in the digital era, particularly amid the increasing need for technological literacy among the elderly population. This study aims to analyze the factors influencing older adults’ participation in community based digital education programs, with a focus on technological adaptability and educational equity. The research employed a mixed methods approach, involving a sample of 300 questionnaire respondents and 40 semi-structured interview participants. Quantitative data were analyzed using regression to identify relationships among variables, while qualitative data were analyzed thematically to explore participants’ experiences, barriers, and support needs in greater depth. The findings indicate that user friendly features, such as adjustable font sizes and voice based navigation, as well as social features such as video calling, significantly enhance participation and reduce feelings of loneliness among older adults. Qualitative findings identified major barriers, including health limitations, device accessibility, low self confidence in technology use, and insufficient ongoing training support. The study concludes that inclusive design, integrated social support, and continuous training are essential in promoting digital inclusion and well being among older adults. The implications of this study provide recommendations for technology developers, educators, and policymakers to design digital learning environments that are more equitable, adaptive, and empowering.